Empirisme dan Falibilisme dalam Filsafat Matematika: Sebuah Kajian Epistemologis dan Implikasinya dalam Pendidikan Matematika - Tadqiroh, Alfiatun; Kusuma, Anggun Badu (Griya Journal of Mathematics Education and Application, 2025)
The philosophy of mathematics plays a crucial role in explaining the origins and status of mathematical knowledge. In the context of mathematics education, epistemological understanding is increasingly relevant, given the persistent dominance of absolutist views that regard mathematics as a certain and final body of knowledge. However, approaches such as empiricism and fallibilism offer alternative perspectives that are more reflective and dynamic. This study aims to explore the philosophical ideas of empiricism and fallibilism in mathematics and analyze their implications for mathematics education. The research employs a systematic literature review with a thematic analysis approach to identify key themes from each perspective and their potential contributions to educational practice. The findings reveal that empiricism emphasizes the role of concrete experience in the formation of mathematical knowledge, while fallibilism highlights the open and non-absolute nature of mathematical truth. The integration of these two approaches has the potential to support a contextual learning environment that embraces error and fosters critical thinking. Therefore, this study contributes theoretically to the development of mathematics education that is more humanistic, reflective, and centered on students' understanding.